Aplikasi Biofungisida Berbahan Aktif Trichoderma sp. dan Pupuk Kandang Sapi Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.). - Hotma Sri Wulan Sihombing; Armaini ' '; Yetti ' Elfina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aim to knows the effect of interaction of biofungicide active ingredient Trichoderma sp. with cow manure and best doses of biofungicide and best doses of cow manure on cocoa seedings growth (Theobroma cacao L.). This Research was conducted in Plant Laboratory, Disease Laboratory and experimental field faculty of agriculture, Riau University on Bina Widya Campus Km 12,5 sub-district of Simpang Baru, district of Tampan, Pekanbaru. This research was conducted from August to November 2015. This research used Completely Randomized Design (CRD) factorial that consisting of two factors. The first factor is the Trichoderma Biofungisida (B) consists of two levels            (0 and 25) g/polybag and second factor is the cow manure (P) consists of five levels (30%, 40%, 50%, 60% and 70%) /polybag. Both these factors resulted in 10 treatsment combinations, each combination made three replications, so that there are 30 experimental units. Each experimental unit consisted of two plants, so the total crop was 60 plants. Parameters measured were seedling height, number of leaves, stem convolution, ratio of crown roots  and dry weight. Data obtained from the research results were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. Based on the research the result showed that the treatment Trichoderma biofungisida and cow manure significant on seedling height, number of leaves, stem convolution, dry weight and had no  significant on ratio of crown roots. Treatment of Trichoderma biofungisida burnt 25 g/polybag and cow manure 50% – 60%  /polybag can be recommended to get the growth of cocoa’s seedling. Keywords : cocoa breeding, Biofungicide, cow manure, Trichoderma sp.